Evaluasi Struktur SRPM Gedung 10 Lantai Sesuai Peraturan Gempa SNI 1726:2019 - Wulandari, Shinta Berlinda; Sutriono, Bantot (Politeknik Negeri Lhokseumawe, 2024)
Abstract — An earthquake is a natural phenomenon that releases energy to create seismic waves. Building damage due to earthquake lateral forces can be prevented or minimized if it can estimate the behavior of structural performance when the building is planned. In this research, the author evaluates a 10-story SRPM structure because it previously used the SNI 1726: 2012 earthquake regulations, so it is necessary to conduct an evaluation that focuses on the main structural elements to be able to determine the displacement and drift due to the influence of earthquake forces according to the latest SNI 1726: 2019 standards. This research results in, the X-direction displacement value for SNI 1726:2019 is greater than the X-direction displacement value for SNI 1726:2012 and the Y-direction displacement value for SNI 1726:2012 is greater than the Y-direction displacement value for SNI 1726:2019. The X and Y direction drift values for SNI 1726:2012 and SNI 1726:2019 do not exceed the permit drift value.